Mediadores inflamatórios, sarcopenia, funcionalidade e dor lombar aguda em idosas: estudo longitudinal back complaints in the Elders-Brasil - Barbara Zille de Queiroz (2015)
Low back pain (LBP) is a relevant complaint, with great economic impact on public health and impact on the functionality of the elderly. Literature shows increased levels of inflammatory mediators by assessing local tissue in adults with LBP. Cytokines locally modulate synaptic activity by increasing the efficacy of neural transmission and reducing the nociceptive-response threshold. With aging there is a chronic inflammatory process, with an increased production of inflammatory mediators, even in the absence of disease. There is a gap in the literature relative to studies about LBP in the elderly, especially about its relationship with the inflammatory mediators. The aim of this thesis was to investigate the impact of inflammatory mediators plasma levels in the functionality and pain in elderly with acute LBP at baseline and at 6 and 12 months follow-up. A longitudinal study was conducted with 155 elderly women (70.7 ± 5.3 years), it was a subsample of the epidemiological study Back Complaints in the Elders (BACE) -Brazil. Enzyme-linked immunosorbent assays were used to measure plasma levels of inflammatory mediators (tumor necrosis factor (TNF) -, soluble TNF- receptor (sTNF-R1), interleukin (IL) -1 and IL-6); LBP was assessed by the numerical pain scale (END) and the McGill pain questionnaire; the functionality was assessed by gait speed and Rolland Morris Disability Questionnaire. Handgrip was evaluated by Jamar dynamometer, and the elderly were categorized by the presence and absence of risk for sarcopenia according to European Working Group on Older People in Sarcopenia (EWGSOP). The Geriatric Depression Scale was used for screening of depressive symptoms and the physical activity level was measured using the International Physical Activity Questionnaire (IPAQ)-Short. The results were presented in three studies. The aim of the first study was to compare the pain, functional performance and levels of inflammatory mediators (TNF-, sTNF-R1, IL-1- e IL-6) among elderly women with and without risk for sarcopenia. 52.26% were at risk for sarcopenia and showed higher plasma levels of sTNF-R1 (p = 0.037), higher LBP severity and frequency (p = 0.043; p = 0.037) and worst functional performance (p = 0.011) compared to the elderly women without risk for sarcopenia. The second study was a cross-sectional study to investigate the association between plasma levels of TNF-, sTNF-R1, IL-6 and IL-1-, clinical variables, severity and qualities of pain, and disability in elderly women with acute LBP. Depressive symptoms and IL-6 were explained 20.9% of the variability of the LBP qualities. TNF-, sTNF-R1, education level, body mass index (BMI) and depressive symptoms explained 8.4% of the variability of the LBP severity. TNF- levels, education, BMI, depressive symptoms, severity, qualities and frequency of LBP explained 48.6% of the disability assessed by Rolland Morris. There were no association between the severity and frequency of the LBP and the inflammatory mediators. The third study was a longitudinal study to determine the natural course of pain and plasma levels of inflammatory mediators in a follow-up of 6 and 12 months, in addition the aim was to verify the longitudinal association of inflammatory mediators and the LBP recovery. There was a decrease in mean severity of LBP (P=0.033) and in the IL-6 and TNF- (p<0.001) levels over time. There was an increase in sTNF-R1 (p<0.001) levels in the first year after an acute episode of LBP. The probability of occurrence of pain relief at 12 months follow-up was 2.22 times higher in elderly women who had lower levels of IL-6 (less than 1.58 pg/mL) at baseline. The results of the studies showed that there is an association between plasma levels of inflammatory mediators, LBP and functionality. In addition, elderly women with acute LBP at risk for sarcopenia had higher levels of inflammatory mediators, more pain and worse functional performance than elderly women without risk for sarcopenia. The 12 months follow-up showed a favorable prognosis with a reduction of inflammatory mediators and LBP severity. Our findings support the concept that pro-inflammatory cytokines may promote pain. Longitudinal data showed the relationship between inflammation and LBP by establishing that the cause (low IL-6 plasma levels) preceded the outcome (LBP recovery). The evaluated biomarkers pointed to the understanding of the mechanism of action of cytokines, pain, sarcopenia and functionality, and could contribute to the research and therapeutic interventions of LBP in the elderly. The silent action of these peripheral mediators should be considered in the assessment and treatments of elderly patients with LBP.